Summative Evaluation of The Curriculum Literacy Program for Teachers - Erdem, Serdar; Toy, Banu Yucel (PAMUKKALE UNIV, 2025)
In this study, it was aimed to reveal the findings regarding the summative evaluation of the Curriculum Literacy Training Program for Teachers. This in-service training program, prepared by the researchers, was applied to 24 volunteer teachers working at primary and secondary school levels as synchronous online learning in 6 days and 18 hours. In the qualitative dimension of this evaluation research, which was designed in the case study design, the data obtained from the training evaluation forms filled out by the participant teachers and the interviews with the participants were analyzed by the content analysis method. In the quantitative dimension of the study, participants' lesson plans were evaluated via the lesson plan evaluation form and the Curriculum Literacy Self-Efficacy Scale administered to the participants just before the training and five weeks after the completion of the training were analyzed using paired groups t-test. According to the findings, it can be stated that the participant teachers reached the objectives of the program to a great extent at the end of the implementation and that participants' professional competencies regarding curriculum and implementation improved. Also, it was determined that the positive opinions of the participant teachers regarding the elements of the training program were much more prominent. The results of the pretest and post-test analyses of the scale revealed that the participants' curriculum literacy self-efficacy levels increased significantly.
Keywords: Curriculum literacy; In-service training; Summative evaluation; IMPLEMENTATION; Education & Educational Research